2019
DOI: 10.3390/ijerph16234731
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Mammographic Breast Density in California: A Strategy to Reduce Breast Cancer Risk

Abstract: State legislation in many U.S. states, including California, mandates informing women if they have dense breasts on screening mammography, meaning over half of their breast tissue is comprised of non-adipose tissue. Breast density is important to interpret screening sensitivity and is an established breast cancer risk factor. Environmental chemical exposures may play an important role in this, especially during key windows of susceptibility for breast development: in utero, during puberty, pregnancy, lactation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Previous literature supports the link between socioeconomic factors and their effects on health ( 102 107 ). One study found that maternal education level, compared to paternal education level, may be less important in influencing the risk of low birthweights, a positive association for breast cancer risk ( 108 ), in black families ( 106 ). Additionally, childhood socioeconomic status may also contribute to health outcome in adulthood ( 102 ) implying intergenerational socioeconomic stresses can contribute to epigenetic modifications and poor health.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature supports the link between socioeconomic factors and their effects on health ( 102 107 ). One study found that maternal education level, compared to paternal education level, may be less important in influencing the risk of low birthweights, a positive association for breast cancer risk ( 108 ), in black families ( 106 ). Additionally, childhood socioeconomic status may also contribute to health outcome in adulthood ( 102 ) implying intergenerational socioeconomic stresses can contribute to epigenetic modifications and poor health.…”
Section: Discussionmentioning
confidence: 99%
“…More robust methods for measuring and reporting breast density in women could aid in identifying environmental agents that alter MD and the associated features that contribute to breast cancer. For example, research linking clinically reported MD scores (now mandated in at least 24 states [ 199 ]) with monitoring of environmental chemicals through the Environmental Protection Agency’s (EPA) National Air Toxics Assessment [ 200 ] has permitted measurement of epidemiological associations between environmental exposures and MD in large populations [ 188 , 201 ]. Similar use of environmental chemical monitoring data, such as those gathered through the Unregulated Contaminant Monitoring Rule for drinking water and the Agency for Toxic Substances and Disease Registry’s PFAS Multi-Site Study, could enable epidemiological associations between chemical exposures in water and MD, as well as lactation, puberty, and breast cancer.…”
Section: Mammary Densitymentioning
confidence: 99%
“…However, these associations were found in rather heterogeneous populations and should be interpreted with caution, particularly the relative degree of influence acute versus chronic stress/anxiety/depression has on risk for breast cancer [ 26 , 27 ]. Another noteworthy environmental risk factor is the role of shift work, particularly working late at night, as a risk factor for breast cancer [ 28 ]. Dysregulation of melatonin and disrupted sleep schedule, predominantly observed in low-income women working shift patterns, have been shown to increase risk for cancer [ 6 ].…”
Section: Primary Prevention Of Breast Cancer: a Brief Review Of Rementioning
confidence: 99%